Trend Analysis of Rainfall Erosivity in Liaoning Province (2003-2022) using the Mann-Kendall Test - Han Yu; Zhao Lian (E3S Web of Conferences)
To investigate the spatiotemporal dynamics of rainfall and its erosivity in Liaoning Province under a changing climate, this study utilized daily and monthly precipitation data from 2003 to 2022. A simplified daily rainfall erosivity model, distinguishing between cold and warm seasons, was applied in conjunction with the Mann-Kendall trend test and the Theil-Sen slope estimator to systematically quantify the spatiotemporal heterogeneity of rainfall and associated erosivity. Over the study period, annual rainfall and rainfall erosivity in Liaoning Province exhibited no statistically significant directional trends (P > 0.05). However, rainfall amount emerged as a critical determinant of erosivity; linear regression analysis revealed a strong positive correlation between annual average rainfall erosivity and annual average rainfall amount (R² = 0.565, P < 0.01), confirming rainfall quantity as a key predictor of erosive potential. These findings offer a scientific foundation for dynamic monitoring and mitigation strategies targeting regional soil erosion.